The Role of Iron Adequacy for Maternal and Fetal Health - Sungkar, Ali (World Nutrition Journal, 2021)
Nearly half of pregnant women in the world are reported to suffer anemia. And most of them are caused by iron deficiency, while the others by folate, vitamin B12 or vitamin A deficiency, chronic inflammation, parasite infections and hereditary disorders. Anemia in pregnant women is characterized when < 11 g / dL or any time during pregnancy. And when followed by low iron, it's called iron deficiency anemia. Iron plays an important role in many metabolic processes by transporting oxygen and allowing cells to generate energy. Low iron levels during pregnancy leading to anemia, related to an heightened risk of mother and fetus disease. Iron deficiency anemia can affect fetal development and persist long-term, while mild and serious pregnancy anemia can lead to premature birth, maternal and child mortality, bleeding, and infectious disease. The iron requirement during pregnancy exceeds 1000 mg for red cell expansion, 300 mg – 350 mg for developing fetus and placenta, and 250 mg for variable blood loss at delivery. Iron adequacy during pregnancy can be assured by proper nutrition, iron supplementation and fortification, and intravenous iron or blood transfusion. Iron supplementation is only enough to cover the prenatal iron requirements. Summary: Iron deficiency leading to anemia, rising risk of negative pregnancy outcomes. To meet increasing iron requirements during pregnancy including iron supplementation, fortification of staple iron foods, and intravenous iron or blood transfusion if required.